Intercalation assembly of kojic acid into Zn-Ti layered double hydroxide with antibacterial and whitening performances - Wang, Xin-Rui; Cheng, Hui-Min; Gao, Xue-Wei; Zhou, Wei; Li, Shu-Jing; Cao, Xue-Li; Yan, Dongpeng (Chinese chemical letters, 2019)
The inhibitor of melanin and the bacteriostatic agent kojic acid was inserted into Zn-Ti layered double hydroxide (LDH) by anion-exchange reaction. The structure, slow release, antibacterial and skin whitening activity were studied. [Display omitted] A melanin synthesis inhibitor and bacteriostatic agent, kojic acid (KA) has been intercalated into Zn-Ti layered double hydroxide (LDH) by an anion-exchange reaction. The structure and the thermal stability of the samples were characterized by XRD, FT-IR, TG-DTA and SEM. The study of KA release from ZnTi-KA-LDH in phosphate buffered solution (pH 5) implies that ZnTi-KA-LDH is a better controlled release system than pure KA. Meanwhile, the mechanisms of slow release were assessed by using four commonly kinetic models. The antimicrobial activity of ZnTi-KA-LDH was tested against three kinds of bacteria. The inhibition of l-dopa oxidation was tested to verify its skin whitening effect. The studies suggest that the kojic acid intercalated LDHs has the potential application as a safely functional composite in cosmetic.